Modeling of Flood Control Using the Siphon Method to Optimize Gravity-Driven Flow in Open Channels - Elhaq, Dea Annisa; Gunawan, Taufik Ari; Juliana, Imroatul C (Fakultas Teknik Universitas Tanjungpura, 2025)
This study evaluates the hydraulic performance of Palembang